A Model for Financial Control in Metropolitan Municipalities of Iran - Jafar Babajani; Mohammad Taghi Taghavifard; Reza Ghanbarian (بررسی‌های حسابداری و حسابرسی, 2022)
Objective: Providing a model for financial control according to the legal basis and environmental characteristics of activities in metropolitan municipalities of Iran is the main purpose of this study. Developing a model of financial control in the municipalities provides the necessary basis for evaluating the receipt and consumption of resources based on the approved goals and in the anticipated destinations. Methods: In this study, the dimensions, components and indicators of providing financial control model in metropolitan municipalities has been identified by using library studies and fuzzy Delphi method. After screening the indicators by using scree test, Fuzzy hierarchical analysis method has been used to determine the weight of each factor and provide a model of financial control in Tehran municipality and other Iranian metropolitan municipalities. To collect data, questionnaires had distributed in two stages between 40 financial managers of Tehran Municipality and 20 financial experts of Mashhad, Isfahan, Shiraz, Kerman and Urmia municipalities. Finally, the proposed financial control model has been validated through structured interviews with 5 independent experts and Spearman test. Results: This study has been provident a model of financial control in the municipality of Tehran and other metropolises.  This Financial control model consists of four components: Predict and identify the Financial Supervisors, Predicting the provisions of financial supervision in laws and regulations, designing procedures and methods for exercising financial control in executive processes and Establish financial control infrastructures. Audit Committee, financial controller, External and Internal Auditors are among the most important financial supervisors within the city administration. Also, The National Inspection Agency and the Ministry of Interior are the most important Financial External Supervisors of municipalities. Clear determination of accountable and levels of accountability, separation and explanation of the relationship between authorized spending authorities and oversight agent, oversight of resource and revenue earning are also among the most important variables related to the legal requirement of financial control in municipalities. Control procedures and financial supervision in municipalities can be divided into six main areas: design and implementation of budget controls, use of accounting control methods, evaluation of internal control systems, financial and compliance audits, design and measure financial performance, transparency and open access Citizens. According to the results of this study, transparency and open access to information for citizens is the most important indicator of this sector. Development of a strategic plan to combat fraud and corruption in municipalities, emphasis on the use of information technology in transactions and the use of computer-assisted audit and inspection tools and methods are among the most necessary infrastructure in the implementation of financial control. Conclusion: Financial and performance controls are two main dimensions of control model of Tehran Municipality and other metropolises that together provide the ground for fulfilling the responsibility of urban management accountability. Designing a model of financial control in the municipalities of Iran's metropolises ensures receipt and consumption of resources to achieve the approved goals.